Pengaruh Model Learning Cycle 7E Terhadap Hasil Belajar Fisika Siswa Kelas XI SMAN 8 Mataram - Eti Sulastri; Hikmawati Hikmawati; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2018)
This study aims to determine the effect of learning cycle 7E model on physics learning outcomes of students of class XI SMAN 8 Mataram. The type of this research is experimental research with pretest-posttest control group design. The population in this study is all students of class XI SMAN 8 Mataram academic year 2017/2018. Sampling was done by purposive sampling technique, with class XI MIA 1 students as experiment class and XI MIA 2 class student as control class. The instruments used are multiple choice test and observation sheet. Based on the result of research, the average value for pretest of experiment class and control class is 26,783 and 28,333 while for the average of post-test of experiment class and control class is 60,696 and 52,667. The research hypothesis was tested by t-test with a significant level of 5%. Data of learning result analyzed by using t-test of two parties obtained taccount equal to 2,071 and ttable equal to 1,679 at degree of freedom is 45. According to the criteria of the hypothesis test, if taccount greater than ttable, then Ho is rejected and Ha accepted. So it can be concluded that there is influence of Learning Cycle 7E model to physics learning result of class XI SMAN 8 Mataram.